2020
DOI: 10.3390/ijerph17082653
|View full text |Cite
|
Sign up to set email alerts
|

High Physical Self-Concept Benefits on School Adjustment of Korean Student-Athletes

Abstract: Successful adjustment of student-athletes to their school is an internationally relevant issue. In Korea, school-athletes abandon their athletic activity at a rate of over 40%, suggesting an urgent need to develop measures that allow them to balance sports and academic life. Therefore, this study aimed to investigate the effect of physical self-concept on school adaptation among student-athletes. We analyzed data from 589 student-athletes, including sex and award-winning career as covariates. Then, reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Additionally, female students often have a higher academic self-concept (AS) [18], and while boys with high academic achievement tend to be happier, girls with high academic achievement tend to be more satisfied [19]; thus, adolescents have AS as a vital element in paving the way to be well-rated by peers [20]. Notwithstanding the effects of AS, physical self-concept (PS) influences adolescents' psychological needs more than any other dimension [21,22] and enables individuals to be more likely to succeed in school adjustments [23].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, female students often have a higher academic self-concept (AS) [18], and while boys with high academic achievement tend to be happier, girls with high academic achievement tend to be more satisfied [19]; thus, adolescents have AS as a vital element in paving the way to be well-rated by peers [20]. Notwithstanding the effects of AS, physical self-concept (PS) influences adolescents' psychological needs more than any other dimension [21,22] and enables individuals to be more likely to succeed in school adjustments [23].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that moderate-to high-intensity exercise signi cantly reduced depressive responses related to school adjustment, so adolescents who exercised more were less likely to have school adjustment problems [44]. One study found that students who participated in regular physical activity had a comprehensive understanding of their bodies, and their selfesteem, sense of accomplishment, and other psychological indicators were higher, which positively affected school adjustment [45]. Regular physical activity not only strengthens the body and shapes the personality but also enables adolescents to stimulate their sense of teamwork, develop interpersonal communication skills, and enrich their skills and techniques for dealing with and solving problems during the practice of participation in physical exercise, to comprehensively improve the adaptive ability of social interaction, handling, and interpersonal relationships, and to reduce the externalization of problematic behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Middle school is a period of rapid physical, social, and emotional development for students, which may increase loneliness, stress, depression, and anxiety. 72 On the one hand, girls are easier than boys to adapt to the social relationship between the class and peers, 73 and are more sympathetic, friendly, caring for others and other prosocial psychological characteristics, so they are easier to interact with friends and obtain close friendship. Furthermore, they have good interpersonal skills, 37 which promote PSB; On the other hand, it may also be because girls’ judgment ability, 74 self-control ability 75 and emotion perception recognition 76 are significantly higher than boys’, thus they have good emotional intelligence and promote their prosocial behaviors.…”
Section: Discussionmentioning
confidence: 99%